PEMUTlHAN KAYU DUN.JING (PARASERIANTHES FALCATARIA (L.) NIELSEN). DENGAN METODA RENDAM DAN LABUR - Sri Rulliaty (Jurnal Penelitian Hasil Hutan, 1990)
Tlae effect of chemical concentration and method of bleaching on the wood quality  i8 reported in thia paper. The mmpla   material co,..;.tetl of 40 piet:u jeur4/ing wood (Partueriantha  (alcataria (L.) Nisllen.) meauri"I J cm by 2 cm by 30 cm rapectiwly~ AU 1amplu  UJmt   divided  into  aeuen group& The /int   three grou,,.  were 1oaked in Ozalic acid and Sodium layd,._ib  iolutlone of  l"     SS   and B'A rapecti~ly.  The aecond three ttrou'DI were aleo malled in. Hydrogen perozide and Sodium hydrozide  eolutione of the above .concentration&  The lat  one group roae lmlalaed  with 8<H> Hydro- gen perozide  and  10~  Sodium  hydrozide  iolutione.   Variable rapona    oMrwd    were brilhtnea,  chemical compound penetration,  occurrence of fuzzy   grain and compreaion parallel to the grain.                                         •The raulb   ,..,led. that .ioalrlng  of jeur4Ji1111 wood in Hydrogen perozide and Sodium hydrozide  at 6~  concentra• tion  ahowed the bat   brWhtnea, a  well a  bruahi1111 with  the mme chemical compound at 30CJ, and 1 ~   concentration retpeetively.  The  taJer018 •peMtration  of  tlaae  chemieal compounda into  wood aubdrwte roere J  mm. M•anwhik; the eoaking method in O:callc acid and Sodium hydrozide  decreaeedthe compreesionparallel to the grain aignificantly. p;,,,...thermore the chemical compou~ """d for  bleaching the jeu.,,,ii11/l wood did not affect (uny    grain defect.